You Do What You See: How Witnessing Physical Violence Is Linked to Violent Behavior Among Male African American Adolescents. Issue 2 (June 2016) - Thomas, Alvin; Caldwell, Cleopatra H.; Assari, Shervin; Jagers, Robert J.; Flay, Brian
African American boys are more likely than same-aged counterparts to live in disadvantaged neighborhoods characterized by exposure to physical violence, lower socioeconomic status, poor parent education, and acts of violence. The current study used structural equation modeling to test the associations between witnessing violence, peer and parent expectations, peer behaviors, self-efficacy to avoid violence, and violent behavior as the outcome. Results suggest that African American boys who witnessed physical violence are more likely to engage in violence themselves. Peer and parent violence expectations, peer violence, and adolescent's self-efficacy to avoid violence mediate this. These findings suggest potential for prevention of violent behaviors through modification of norms of male African American adolescents at risk for witnessing violence in their daily life.